Marketing management : an Asian perspective - Kotler, Philip author; Keller, Kevin Lane, 1956- author; Tan, Chin Tiong, author; Ang, Swee Hoon, author; Leong, Siew Meng, author (Harlow : Pearson Education Limited, 2018)
PSZKLL